Overexpression of a member of the pentraxin family (PTX3) in human soft tissue liposarcoma - Willeke, Frank; Assad, A.; Findeisen, Peter; Schromm, Eike-Alexander; Grobholz, Rainer; Gerstenbergk-Helldorf von Zech, Bolko von; Mantovani, A.; Peri, S.; Friess, H. H.; Post, Stefan; Knebel Doeberitz, Magnus von; Schwarzbach, Matthias (European journal of cancer, 2006)
A unique feature of human soft tissue liposarcoma is a stable (12;16)(q13;p11) translocation observed mainly in myxoid and roundcell liposarcomas. This translocation results in FUS/CHOP fusion transcripts with a corresponding oncogenic protein. We hypothesised that genes downstream of FUS/CHOP might serve as attractive candidates for novel tumour associated antigens. Among a panel of analysed genes, only pentraxin related gene (PTX3) demonstrated high expression in liposarcomas as compared to normal tissues. The analysis of RNA and protein expression demonstrated concordant results. However, the level of RNA and protein overexpression did not correlate in all cases. Finally, PTX3 expression was not related to presence of a FUS/CHOP fusion transcript within the liposarcoma tissues. PTX3 has been associated with adipocyte differentiation and now, additionally, is characterised by a markedly increased expression in human soft tissue liposarcoma. This finding mandates further research efforts to clarify the exact role of PTX3 in liposarcoma oncogenesis.
Gesehen am 30.05.2022